Never caught : the Washingtons' relentless pursuit of their runaway slave, Ona Judge - Dunbar, Erica Armstrong (37 Ink/Atria, 2017)
"A revelatory account of the actions taken by the first president to retain his slaves in spite of Northern laws profiles one of the slaves, Ona Judge, describing the intense manhunt that ensued when she ran away,"--NoveList.